Extreme Energy Events: an extended multi purpose cosmic ray observatory. (February 2020) - Gnesi, I.; Abbrescia, M.; Avanzini, C.; Baldini, L.; Baldini Ferroli, R.; Batignani, L. G.; Battaglieri, M.; Boi, S.; Bossini, E.; Carnesecchi, F.; Cicalo, C.; Cifarelli, L.; et al.
Abstract: EEE is an extended cosmic ray observatory, covering more than 10 degrees in latitude and longitude. The relative distances between clusters of telescopes reached the 1200 km, allowing the search for rare long distance correlations between cosmic showers. On the other side each EEE telescope is capable of measuring the flux of secondary particles, opening to the study of low energy phenomena such as solar activity and Forbush decreases. An introduction to the observaotry and updates on the main scientific results are presented. Last updates on the searches for rare correlated showers, with a set of long distance correlation candidate events are also reported.